In vitro evaluation of anticancer potentials of lupeol isolated from Elephantopus scaber L. on MCF-7 cell line - Daisy Pitchai; Anita Roy; Cybil Ignatius (Wolters Kluwer Medknow Publications, 2014)
Lupeol is a triterpenoid, present in most of the medicinally effective plants and possess a wide range of biological activity against human diseases. The present study aims at evaluating the anticancer potentials of lupeol, isolated from the leaves of Elephantopus scaber L. and thereby explores its action on key cancer marker, Bcl-2. The effect of lupeol on the cell viability of MCF-7 was determined by MTT and lactate dehydrogenase assays at different concentrations. The efficacy of the compound to induce cell death was analyzed using AO/EtBr staining. Phase contrast microscopic analysis provided the changes in cell morphology of the compound treated normal breast cells (MCF-10A) and MCF-7 cells. The expression of Bcl-2 and Bcl-xL proteins in the normal, cancer and lupeol treated cancer cell was analyzed by western blotting. Lupeol induced an effective change in the cell viability of MCF-7 cells with IC 50 concentration as 80 μM. Induction of cell death, change in cell morphology and population of the cancer cells was observed in the lupeol treated cells, but the normal cells were not affected. The compound effectively downregulated Bcl-2 and Bcl-xL protein expressions, which directly contribute for the induction of MCF-7 cell apoptosis. Conclusion: Thus, lupeol acts as an anticancer agent against MCF-7 cells and is a potent phytodrug to be explored further for its cytotoxic mechanism.